First record of the genus Tatia (Siluriformes: Auchenipteridae) in freshwaters of Argentina - Almirón, Adriana; Casciotta, Jorge; de las Mercedes Azpelicueta, M.; Aichino, Danilo; Benítez, Mauricio; Piálek, Lubomír; Doubnerová, Klára; Říčan, Oldřich (My University, 2014)
The genus Tatia is recorded for the first time from Argentina in Misiones and Corrientes Provinces. Tatia jaracatia was captured only in the arroyo Deseado, río Iguazú basin, and Tatia neivai has been caught in several streams (tributaries of río Paraná) Piray Guazú, Garuhapé, Tabay, Garupá, and also from the río Paraná in Puerto Nemesio Parma and Ituzaingó
Keywords: genus Tatia (Siluriformes: Auchenipteridae); Argentina